ANALISIS KULTUR ORGANISASI DALAM MENENTUKAN GAYA KEPEMIMPINAN EFEKTIF - Darmawan Darmawan (JURNAL LENTERA BISNIS, 2012)
The contemporary definition of organizational culture (OC) includes what is valued, the dominant leadership style, the language and symbols, the procedures and routines, and the definitions of success that characterizes an organization. OC represents the values, underlying assumptions, expectations, collective memories, and definitions present in an organizationCameron and Quinn (2002) have developed an organizational culture framework built upon a theoretical model called the "Competing Values Framework." This framework refers to whether an organization has a predominant internal or external focus and whether it strives for flexibility and individuality or stability and control. The framework is also based on six organizational culture dimensions and four dominant culture types (i.e., clan, adhocracy, market, and hierarchy) and generated an "Organizational Culture Assessment Instrument (OCAI)" which is used to identify the organizational culture profile based on the core values, assumptions, interpretations, and approaches that characterize organizations (Cameron & Quinn, 2002).The competing values framework can be used in constructing an organizational culture profile. Through the use of the OCAI, an organizational culture profile can be drawn by establishing the organization's dominant culture type characteristics.